(untitled) (Journal of the Bangladesh Agricultural University, 2012)
To study the effect of months, seasons, age and sex on visceral leishmaniasis (VL) in human, data were collected during March 2010 through February 2011 from the register book of Upazila Health Complex (UHC) of Trishal, which is an endemic region for VL in the Mymensingh district. Besides, 70 blood samples were collected from suspected VL human patients to compare microscopy with rK39 immunochromatographic strip test. Additionally, 50 cattle blood samples were also collected from houses with active or recently-treated VL patients to determine the possible animal reservoir of VL through rK39 strip test. Of the suspected VL patients in the UHC registered book, 43.8% were seropositive. The percentages of seropositive cases were higher in September (73.3%), November (67.2%) and August (65.5%) than in May (18.5%), June (27.5%) and March (36.7%). The rainy season (58.4%) and the winter season (50.6%) showed higher seropositive than the summer (30.7%) season which was significant (p? 0.001). Hospital cases of VL were significantly (p?0.05) higher in 3-14 years (49.3%) and 15-45 years (43.5%) than in children <3 years (32.1%) and adults aged >45 years (33.6%) people. The estimated sensitivity of rK39 strip test and microscopic examination were 100% and 58.8%, respectively and the specificity were 72% and 100%, respectively. Only two cattle blood samples were found positive to rK39 strip test. Our present study indicates that rK39 strip test is superior to the diagnosis of VL compared with parasitological confirmation by direct microscopy of the peripheral blood. Further works are needed to focus on molecular approaches for diagnosis and epidemiological study of VL, sand flies investigation and to confirm the cattle as animal reservoir for VL transmission. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12097 J. Bangladesh Agril. Univ. 10(1): 7986, 2012